Manajemen Asset Sebagai Upaya Pelestarian Bangunan Cagar Budaya Di Kota Surabaya (Studi Pada Dinas Kebudayaan Kepemudaan Dan Olah Raga Serta Pariwisata Kota Surabaya) - Wahyudianto, Ferry; Hardjati, M.AP, Dra. Susi (Irpia : Jurnal Ilmiah Riset dan Pengembangan, 2023)
Asset management involves managing and providing guidance on the acquisition, utilization, and disposal of assets to maximize benefits and mitigate risks throughout their lifespan. This study focuses on the management of cultural heritage building assets, specifically those located in Surabaya,a city known for its unique characteristics. Determining the monetary value of these assets is extremely challenging, as cultural heritage assets cannot be replaced or replicated. Cultural heritage building asset management encompasses the management of sites and artifacts associated with cultural heritage.It serves as a crucial decision-making tool for public administrators in conserving government- protected cultural heritage buildings. Consequently, the management of cultural heritage building assets involves a comprehensive process that includes identification and assessment, resource allocation, protection, conservation, presentation, and monitoring. The research conducted for this study is descriptive and qualitative in nature. It employsvarious data collection techniques, including observation, interviews, and documentation. The researchtakes place at the Department of Youth Culture, Sports, and Tourism in the city of Surabaya. To gatherinformation, the study refers to Siregar's theory (2004) on the five dimensions of service quality asproposed by Parasuraman. The study aims to update and enhance the existing knowledge by focusingon five specific objectives: 1.Asset Inventory, Conducting a comprehensive inventory of the assetsinvolved. 2. Legal Audit: Evaluating the legal aspects and compliance related to the assets. 3. AssetValuation: Determining the value of the assets in question. 4. Asset Optimization: Identifying strategiesto maximize the utilization and potential of the assets. 5. Supervision and Control: Establishing effectivemechanisms for overseeing and maintaining control over the assets. By addressing these studyobjectives, the research intends to improve the understanding and management of cultural heritagebuilding assets within the context of the Department of Youth Culture, Sports, and Tourism in Surabaya.The study conducted is of a descriptive and qualitative nature, utilizing data collection techniques such as observation, interviews, and documentation. It takes place at the Department ofYouth Culture, Sports, and Tourism in Surabaya. The research incorporates Siregar's theory (2004) onthe five dimensions of service quality according to Parasuraman to update and enhance existing knowledge. The study focuses on five specific objectives:1.Asset Inventory: Conducting acomprehensive inventory of the assets involved.2.Legal Audit: Evaluating the legal aspects andensuring compliance related to the assets.3. Asset Valuation: Determining the value of the assets underinvestigation.4. Asset Optimization: Identifying strategies to maximize the utilization and potential of the assets.5.Supervision and Control: Establishing effective mechanisms for overseeing andmaintaining control over the assets. By addressing these objectives, the research aims to enhance theunderstanding and management of cultural heritage building assets within the context of the Department of Youth Culture, Sports, and Tourism in Surabaya.